Classification of unipolar and bipolar depression using machine learning techniques. (January 2021) - Suen, Paulo J C; Goerigk, Stephan; Razza, Lais B; Padberg, Frank; Passos, Ives Cavalcante; Brunoni, Andre R
Highlights: Machine learning models might correctly classify between uni and bipolar depression Clinical and sociodemographic information are important predictors Such models can be applied as screening tools in health services Exploring different algorithms according to available dataset may improve results